Repair of the Medial Ulnar Collateral Ligament of the Elbow With Internal Brace Augmentation - Richard F. Nauert MD; Kristin E. Yu MD; Christopher L. Camp MD (SAGE Publishing, 2023)
Background: The medial ulnar collateral ligament (MUCL) is the primary restraint to valgus force across the elbow during throwing. The incidence of MUCL continues to rise, and injuries are common in overhead throwing athletes often leading to elbow pain and instability. While MUCL reconstruction remains the gold standard for high-level throwing athletes with midsubstance tears, MUCL repair remains an option for select athletes and affords good functional outcomes with quicker return to sport compared with reconstruction. Indications: Indications for MUCL repair include acute injuries, proximal or distal avulsions, young and lower demand athletes, non-throwing athletes, or older athletes who may be nearing retirement. Technique Description: An incision is made over the medial elbow from the medial epicondyle to the sublime tubercle. Dissection is carried down to fascia which is split in line with its fibers. The flexor pronator muscle group is bluntly divided, and the ligament exposed. Care is taken to identify and dissect the native ligament. The avulsed portion of the ligament is secured with a 0 FiberWire suture in a running locked whipstitch fashion. The footprint of the avulsed ligament is gently debrided and prepared using a scalpel. The 0-FiberWire suture tails are then loaded onto a suture anchor preloaded with suture tape. This is then secured at the footprint of the ligament. The FiberWires are cut, and the suture tape is then pulled back over the native ligament and fixed at the other attachment site for the ligament. 0-Vicryl sutures are then used to suture the internal brace to the underlying ligament so the construct would move as a single unit. Results: Biomechanical testing has demonstrated that MUCL repair with internal brace augmentation has similar time-zero failure strength when compared with the original Jobe reconstruction technique while also having greater resistance to gapping. In addition, recent literature has shown that well-selected patients can have excellent functional outcomes and quicker return to sport with MUCL repair as opposed to reconstruction. Discussion: Medial ulnar collateral ligament repair with internal brace augmentation can be a successful treatment in the appropriately indicated athlete to allow for good functional results and quicker return to sport. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.